Evaluación docente para la mejora continua en la Unidad Educativa Catorce de Julio J.A.E. en Latacunga. - Cando Chinachi, Verónica Alexandra (2018)
This project is exploratory and descriptive research since the current situation of teacher evaluation was investigated in different circumstances, both institutionally and socially, taking into account the advantages and disadvantages of the evaluation. The primary objective was to describe the current situation of the teachers' evaluation in the Education Unit Catorce de Julio Juan Abel Echeverría "J.A.E." Books, magazines, and websites were examined for the theoretical support of the research, which helped in the establishment of the definitions and concepts of teacher evaluation, as well as a field investigation was carried out when applying the research techniques for the data collection. The survey technique was applied to its respective questionnaire that helped to constitute a clear and real